A Comparative Study Between The Levels of Adropin in Iraqi Women with Metabolic Syndrome and Diabetes - Hussien Assaf, Riyam; Layla Othman Farhan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
By measuring Adropin, fasting blood glucose (FBG), cholesterol, high-density lipoprotein (HDL), triglycerides (TG), low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL) in the sera of Iraqi patients with MetS and type 2 diabetes mellitus (T2DM), the current study was designed to compare some crucial markers in metabolic syndrome (MetS) sera and diabetic patients (T2DM) with control. Twenty female subjects were divided into three groups: group I=40 with MetS and group II=40 with T2DM, and 40 healthy subjects were employed as a control group. Compared to the control group, Adropin levels in the Mets group and T2DM group decreased significantly (p < 0.05). In contrast, none of the patient groups (MetS and T2DM) showed any change compared to themselves. In conclusion, according to the present data, higher levels of FBG, lipid profile, and increased blood pressure (BP) were found in patients with MetS and T2DM. A drop in level could be considered a novel indicator of MetS and T2DM. Compared to T2DM patients, Adropin levels are thought to have a more sensitive diagnostic function than those with MetS and newly diagnosed DM.